PD-1/PD-L1 Blockade: Have We Found the Key to Unleash the Antitumor Immune Response? - Xu-Monette, Zijun Y.; Zhang, Mingzhi; Li, Jianyong; Young, Ken H. (Frontiers in Immunology, 2017)
PD-1−PD-L1 interaction is known to drive T cell dysfunction, which can be blocked by anti-PD-1/PD-L1 antibodies. However, studies have also shown that the function of the PD-1−PD-L1 axis is affected by the complex immunologic regulation network, and some CD8+ T cells can enter an irreversible dysfunctional state that cannot be rescued by PD-1/PD-L1 blockade. In most cancers, except Hodgkin lymphoma (which has high PD-L1/L2 expression) and melanoma (which has high tumor mutational burden), the objective response rate with anti-PD-1/PD-L1 monotherapy is only ~20%, and immune-related toxicities and hyperprogression can occur in a small subset of patients during PD-1/PD-L1 blockade therapy. The lack of efficacy in up to 80% of patients was not necessarily associated with negative PD-1 and PD-L1 expression, suggesting that the roles of PD-1/PD-L1 in immune suppression and the mechanisms of action of antibodies need to be better defined. In addition, important immune regulatory mechanisms within or independent from the PD-1/PD-L1 network need to be discovered and targeted to increase the response rate and to reduce the toxicities of blockade therapies. This paper reviews the major functional and clinical studies of PD-1/PD-L1, including those with discrepancies in the pathologic and biomarker role of PD-1 and PD-L1 and the effectiveness of PD-1/PD-L1 blockade therapy. The goal is to improve understanding of the efficacy of PD-1/PD-L1 blockade, as well as enhance the development of therapeutic strategies to overcome the resistance mechanisms and unleash the antitumor immune response to combat cancer.